Developing climate risk maps and adaptation plans for rice-based production systems in the Philippines - Jeny Raviz; Mary Anne Gutierrez; Cornelia Garcia; Rowena Castillo; Jane Girly Balanza; Michelle Joy Manipol; Rico Locaba; Jon Hellin; Alice Laborte (2023)
Rice-based production systems in the Philippines play a crucial role in food security and are highly vulnerable to climate-related risks such as flooding, drought and high temperatures. CGIAR’s Research Initiative on Climate Resilience (ClimBeR) has been conducting activities to increase the resilience of smallholder production systems in the Philippines to withstand the effects of climate change. One of these is the Climate-Smart Mapping and Adaptation Planning (CS-MAP, [1]). CS-MAP is a participatory mapping approach to identify climate risks, map potentially affected areas and develop location-specific adaptation plans. CS-MAP integrates scientific and local knowledge as the main basis of the participatory process. ClimBeR is implementing CS-MAP in pilot sites in four provinces in the Philippines.